COVID-19 alters the relationship between relational mobility and helping behavior - Zhang, Xiaoxiao; Zhao, Xian; Liao, Gengnan; Huang, Yuanlin; Fang, Xuan (Frontiers in Psychology, 2022)
To determine if helping behavior is affected by cultural-ecological variables such as relational mobility, we investigated the impact of relational mobility on volunteering signup before (Study 1) and during (Study 2) COVID-19 in China via two experiments. In Study 1, we manipulated participants’ relational mobility and found that a greater proportion of participants in the high relational mobility condition volunteered to sign up for another psychological experiment, relative to the low relational mobility condition. In Study 2, the manipulation of relational mobility was embedded in a phone interview, and we found that a high relational mobility condition caused fewer signups for a COVID-19 support program relative to a low relational mobility condition. These results extend our knowledge of the consequences of relational mobility and reveal the importance of ecological variables, including relational mobility and pandemics, in understanding the precedents of helping.